Room Layout and Design Predispose Patient Safety - Fitri Yuni; Husna Yetti; Yuniar Lestari; Hardisman Hardisman; Firdawati Firdawati; Yevri Zulfikar (Newinera Publisher, 2026)
Patient Safety Incidents (IKP) can impact the quality of hospital services. Both globally and nationally, patient safety incidents remain a significant concern. At Prof. HB Saanin Mental Hospital in Padang, the number of patient safety incidents increased from 2022 to 2023. Patient safety incidents should be zero, or there should be no accidents, based on the Decree of the Minister of Health of the Republic of Indonesia number 129/Menkes/II/2008 concerning Minimum Hospital Service Standards. Objective: Analyze the influence of room layout and design on patient safety incidents at Prof. HB Saanin Mental Hospital, Padang. Method: This study used a mixed-methods cross-sectional study of 25 officers involved in patient safety incidents. Bivariate analysis using the Chi-square test was employed to assess the relationship between room layout and design and patient safety incidents, which was further explored through qualitative interviews. Results: The most common type of patient safety incident at Prof. HB Saanin Mental Hospital is unwanted events, accounting for 64% of total incidents and 52% of incidents with high impact. Inappropriate room design was identified in 52% of cases, and inappropriate furniture layout was identified in 84%. Conclusion: Equipment layout and room design influence the occurrence of patient safety incidents in the Prof. HB Saanin Mental Hospital, Padang. Redesigning rooms is a key factor in reducing patient safety incidents at this hospital.